Political economy of the Raj 1914 - 1947; Economics of decolonization in India - "Tomlinson, B R" (London, 1979)
Decolonization is a modern word for an important feature of twentieth-century world history. The ending of colonial rule is not, of course, an exclusively twentieth-century phenomenon, the fall of empires has gone on for almost as long as their rise.
Keywords: India - Economic conditions - 1918 - 1947